PENGARUH MODEL PEMBELAJARAN CLIS TERHADAP HASIL BELAJAR DAN KETERAMPILAN PROSES SISWA KELAS V-B SDN MADE I/475 SURABAYA - LESTARI AYU NINGRAT, SRI (Jurnal Penelitian Pendidikan Guru Sekolah Dasar, 2016)
Abstrak Tujuan dari penelitian ini adalah untuk mengetahui pengaruh model pembelajaran CLIS terhadap hasil belajar dan keterampilan proses IPA siswa  serta peningkatan hasil belajar dan keterampilan proses siswa kelas V-B SDN Made I/475 Surabaya. Penelitian ini menggunakan penelitian kuantitatif metode quasi eksperimen dengan desai penelitian Nonequivalent Control Group Design. Sampel yang digunakan adalah kelas V-A dan V-B dengan jumlah masing-masing 20 siswa. Teknik pengumpulan data yang digunakan adalah tes hasil belajar dan keterampilan proses serta lembar aktivitas guru dan siswa. Hasil penelitian menunjukkan aktivitas guru dan siswa pada pembelajaran mendapatkan persentase lebih dari 80%. Pada pretest hasil belajar siswa yang tuntas hanya 20% sedangkan pada posttest hasil belajar 100% siswa tuntas. Jumlah N-Gain hasil belajar siswa adalah 15,47 dengan rata-rata N-Gain adalah 0,77. Uji beda hasil belajar diperoleh nilai thitung > ttabel (3,958 > 1,685). Artinya, terdapat perbedaan yang signifikan antara gain hasil belajar kelas eksperimen dengan kelas kontrol. Sedangkan pada pretes keterampilan proses siswa yang tuntas hanya 20% dari 20 siswa dan pada posttes keterampilan proses 100% siswa tuntas. Jumlah N-Gain hasil keterampilan proses siswa adalah 15,61 dengan rata-rata N-Gain sebesar 0,78. Uji beda keterampilan proses diperoleh nilai thitung > ttabel (3,068 > 1,685). Artinya, terdapat perbedaan yang signifikan antara gain keterampilan proses kelas eksperimen dengan kelas kontrol.  Kata kunci: model pembelajaran CLIS, hasil belajar, keterampilan proses.    Abstract The purpose of this study is to describe the effect of CLIS learning model towards the learning outcomes and processing skill of the students of V-B in SDN Made I/475 Surabaya and the increase of learning outcomes and processing skill of the students of V-B in SDN Made I/475 Surabaya. This study is a quantitative research using quasi-experimental method and Nonequivalent Control Group Design. The research samples are the class of V-A as control class and the class of V-B as experimental class which consist of 20 students per class. The data collection techniques used are test of learning outcomes and processing skill, and teacher and student observation sheets. The results of this research shows that teacher’s and students’ activities during teaching and learning process managed by using CLIS learning model went well by the percentage of beyond 80%. In the pre-test, students’ learning outcomes show that only 20% of 20 students who are accomplished, while in the post-test, 100% of students are accomplished. The total of N-Gain of students’ learning outcomes reaches 15.47 with the average score of N-gain reaches .77. Based on the test of learning outcomes difference, it can be said that tcount> ttable (3.958 > 1.685). It means that there is a significant difference between the learning outcomes of the experimental class and the learning outcomes of the control class. In pre-test, only 20% of students’ processing skills which are considered accomplished, while in the post-test, 100% of students’ processing skills are all accomplished. The total gain score of the result of the students’ processing skill is 15.61 with the average score of N-Gain reaches .78. Based on the result of processing skill difference test, it was obtained tcount > ttable (3.068 > 1.685). It indicates that there is a significant difference between the gain rate of experimental class’s processing skill and the control class’s processing skill. Keywords: CLIS learning model, Learning Outcomes, Processing Skill